Influence of previous knowledge in Torrance tests of creative thinking - María Aranguren (International Journal of Psychological Research, 2015)
The aim of this work is to analyze the influence of study field, expertise and recreational activities participation in Torrance Tests of Creative Thinking (TTCT, 1974) performance. Several hypotheses were postulated to explore the possible effects of previous knowledge in TTCT verbal and TTCT figural university students’ outcomes. Participants in this study included 418 students from five study fields: Psychology; Philosophy and Literature, Music; Engineering; and Journalism and Advertising (Communication Sciences). Results found in this research seem to indicate that there in none influence of the study field, expertise and recreational activities participation in neither of the TTCT tests. Instead, the findings seem to suggest some kind of interaction between certain skills needed to succeed in specific studies fields and performance on creativity tests, such as the TTCT. These results imply that TTCT is a useful and valid instrument to measure creativity and that some cognitive process involved in innovative thinking can be promoted using different intervention programs in schools and universities regardless the students study field.